RECONSTRUCTION OF THE METHODOLOGY OF LEGAL DISCOVERY IN ISLAMIC LEGAL PHILOSOPHY: A COMPARATIVE ANALYSIS OF THE THEORIES OF BAYANI, TA‘LIL, AND ISTISLAHI IN A CONTEMPORARY CONTEXT - Sari, Muspita; HL, Rahmatiah; Sultan, Lomba (Institut Agama Islam Negeri Bone, 2025)
This article examines the reconstruction of legal discovery methodology in Islamic legal philosophy through a comparative analysis of three classical approaches: Bayani theory, ta‘lil, and istislahi, in response to legal challenges in the contemporary context. The impetus for this research stems from the increasing complexity of modern legal problems such as human rights, digital technology, and ecological justice, which demand a more dynamic methodology of istinb?? al-?ukm, while still being grounded in the authority of revelation. This research uses a qualitative library research method with an Islamic legal hermeneutics approach and descriptive-comparative analysis, which allows for an in-depth study of classical texts and modern literature. . The results of the study show: (1) Bayani theory, which emphasizes text (nash), maintains the continuity of sharia, but needs reinterpretation to be relevant to modern problems; (2) Ta'lil theory, with a focus on rationalization and identification of 'illat (legal reasons), allows for contextual ijtihad, but is prone to subjectivity without a strict methodology; (3) The istislahi theory, which is based on maslahah and maq??id al-shar?‘ah, has proven to be the most adaptive to contemporary issues, although it requires normative boundaries so as not to deviate from the principles of sharia. This research essentially affirms the urgency of reconstructing an integrative methodology for legal discovery, combining the strengths of Bayani, ta‘lil, and istislahi within a comprehensive epistemological framework. This integrative model gives rise to textual, rational, and beneficial Islamic law, responding to the needs of global society without losing the authenticity of revelation. The results of this analysis contribute to the development of Islamic legal philosophy by offering a relevant, dynamic, and socially just paradigm of legal discovery.